Acute Necrotizing Encephalopathy with H1N1 Influenza a Virus Infection - J Gordon Millichap (Pediatric Neurology Briefs, 2010)
A case of acute necrotizing encephalopathy (ANE) associated with the novel H1N1 influenza A virus is reported in a 2-year-old European girl treated at the Catholic University, Rome, Italy.